Correlation between Students’ Attendance and Their Achievement in Online Class - Anwar, Faldi Ferdiansyah; Kamaluddin, Kamaluddin; Siam, Siam (Journal of Teaching of English, 2021)
The objective of this research is to find out the extent of relationship between studentsâ€™ attendance and their achievement in the environment of online class at English Education Department of Halu Oleo University. This research used correlational research design. The population consisted of English Education Department students of Halu Oleo University who enrolled in the third semester of 2020/2021 academic year with a total of 53 students from class A. Subject of the research taken was the whole population of 53 students from class A. The research instrument used was the data record of studentsâ€™ attendance and their achievement in Psycholinguistic Course. To analyze the data, the researcher used both descriptive and inferential statistics. The result of this research reveals that: (1) Studentsâ€™ attendance level is on good level with mean percentage is 88.49 (SD = 13.45); (2) Studentsâ€™ level of achievement results in good level as well with mean is 83.59 (SD = 3.58); (3) The calculation of Spearman Rho Coefficient Correlation (Ï) is 0.076, the significance value is 0.310 > 0.05 (accepted Î± value) and Ï = 0.076 < 0.248 (critical value of Spearman Rho for N = 45), and the equivalence test results in lo_r = -0.2225 for lower bound area which is bigger than -0.7 (Î” > Î”L) and hi_r = 0.3615 in higher bound area which is less than 0.7 (Î” < Î”U). It reveals that the correlation found between studentsâ€™ attendance and their achievement in online class is very weak and statistically not significant yet statistically equivalent. In conclusion, there is no meaningful relationship between studentsâ€™ attendance and their achievement in online class. Â